Language and Vulnerability—A Lacanian Analysis of Respect - Laufer, Laurie; Santos, Beatriz (Frontiers in Psychology, 2017)
Lacan's original approach to language expands the reaches of psychoanalysis. Not limited to a set of technical instructions that guide “treatments of the soul”, lacanian psychoanalysis can be seen as a theoretical toolbox whose utility is multidisciplinary. This paper contends that, by establishing a connection between (i) the idea that subjects are produced by language and bear the mark of the unconscious; and (ii) an approach to the production of symptoms that acknowledges the importance of their sense, lacanian theories enlighten discussions on the theme of vulnerability. We claim that Lacan's description of psychoanalysis as an apparatus that respects the person and (foremost) their symptoms generates evidence of the existence of a kind of recognition that takes into account the vulnerability of a given subject without assigning them to a fixed position of victim. This perspective enriches contemporary debates on the relationship between identity and vulnerability.